Academic Information System Management to Improve Service Quality to Students During the Covid-19 Pandemic at Universities in Jambi Province - Sepryhatin Dioputra; Novi Rukhviyanti; Achmad Pahrul Rodji (Ridwan Institute, 2022)
Higher education with standards and good academic service management quality is the goal of every university's efforts. In Jambi Province, in particular, good management applied to a university is one of the essential factors in improving the quality of service for students, the community, or the university itself. Not a few universities whose academic service quality still does not meet the satisfaction threshold in the assessment, one of which is offline-based services that will usually hinder the delivery of existing information. The universities of UNAMA (University of Stikom Dinamika Bangsa) and IAI Tebo in Jambi Province are universities whose every delivery of academic information focuses on computers and technology. The advantages and disadvantages of the information system that is run, it is necessary to conduct a study to combine each of the advantages and disadvantages of the two universities. By applying qualitative methods, it is hoped will provide helpful research results. The focus of this research is directed at (1). Planning, (2). Implementation, (3). Evaluation (4). Solutions or follow-ups in improving the quality of academic services at universities using the Deming cycle management theory. This study uses a descriptive method with a qualitative approach and data collection by conducting observations, interviews, and documentation studies, so it can be concluded that a complete management information system can be applied to other universities, especially those that are still offline.